Demographic differences in and correlates of perceived body image discrepancy among urban adolescent girls: a cross-sectional study - Lorraine B. Robbins; Jiying Ling; Kenneth Resnicow (BMC, 2017)
Abstract Background Understanding factors related to girls' body image discrepancy, which is the difference between self-perceived current or actual and ideal body size, is important for addressing body-related issues and preventing adverse sequelae. Two aims were to: 1) examine demographic differences in body image discrepancy; and 2) determine the association of body image discrepancy with weight status, percent body fat, physical activity, sedentary behavior, and cardiovascular (CV) fitness among young adolescent girls. Methods The cross-sectional study included a secondary analysis of baseline data from a group randomized controlled trial including 1519 5th-8th grade girls in 24 U.S. schools. Girls completed physical activity and sedentary behavior surveys. To indicate perceived current/actual and ideal body image, girls selected from nine body figures the one that represented how they look now and another showing how they want to look. Girls wore accelerometers measuring physical activity. Height, weight, and percent body fat were assessed. The Progressive Aerobic CV Endurance Run was used to estimate CV fitness. Independent t-test, one- and two-way ANOVA, correlational analyses, and hierarchical linear regressions were performed. Results The majority (67.5%; n = 1023) chose a smaller ideal than current/actual figure. White girls had higher body image discrepancy than Black girls (p = .035). Body image discrepancy increased with increasing weight status (F3,1506 = 171.32, p < .001). Moderate-to-vigorous physical activity (MVPA) and vigorous physical activity were negatively correlated with body image discrepancy (r = −.10, p < .001; r = −.14, p < .001, respectively), but correlations were not significant after adjusting for race and body mass index (BMI), respectively. Body image discrepancy was moderately correlated with CV fitness (r = −.55, p < .001). After adjusting for demographics, percent body fat, but not CV fitness or MVPA, influenced body image discrepancy. Girls with higher percent body fat had higher body image discrepancy (p < .001). Conclusion This study provided important information to guide interventions for promoting a positive body image among girls. Trial registration ClinicalTrials.gov Identifier NCT01503333 , registration date: January 4, 2012.